A dictionary of pharmacology and allied topics - Laurence, D. R. (Elsevier, 1998)
This dictionary spans the practice of pharmacology, and of allied sciences insofar as they are related to it, with particular emphasis on the development, regulation and use of human medicine.
Keywords: Pharmacology -- Dictionaries.; Drugs -- Dictionaries.; Pharmacology.; Drugs.; Drugs -- Testing -- Dictionaries.; elektronické knihy; electronic books